Stability and accuracy of total and free PSA values in samples stored at room temperature. (November 2016) - Forde, J.; Blake, O.; Crowley, V.; Lynch, T.
Abstract Introduction In 2010, an estimated 476, 076 total PSA tests were performed in Ireland, at a cost of €3.6 million with the majority ordered by general practitioners. We aimed to replicate storage conditions at room temperature and see if prolonged storage affected total and free PSA values. Methods Blood samples were taken from 20 male patients in four VACUETTE® Serum Separator tubes (Greiner-Bio-One, Austria) and stored at room temperature (22 °C) for different time intervals (4, 8, 24, 48 h) before being centrifuged and analyzed. Total PSA (tPSA) and free PSA (fPSA) values were determined using the Tosoh AIA 1800 assay (Tokyo, Japan). Results Mean tPSA values were measured at 4, 8, 24 and 48 h with values of 7.9, 8.1, 7.8 and 8.0 μg/L, respectively. Values ranged from −1.26 to +2.53 % compared to the initial 4 h interval reading, indicating tPSA remained consistent at room temperature. The tPSA showed no significance between groups (ANOVA, p = 0.283). Mean fPSA values at 4, 8, 24 and 48 h were 2.05, 2.04, 1.83, 1.82 μg/L, respectively. At 24 and 48 h there was 10.73 and 11.22 % reduction, respectively, in fPSA compared to the 4-h time interval, indicating prolonged storage resulted in reduced fPSA values. After 24 h, there was an 8.8 % reduction in the free/total PSA %. The fPSA showed significant differences between groups (ANOVA, p = 0.024). Conclusions Our recommendation is that samples that have been stored for prolonged amounts of time (greater than 24 h) should not be used for free PSA testing.